Free vibration analysis of magneto-electro-thermo-elastic nanobeams resting on a Pasternak foundation. (22nd February 2016) - Jandaghian, A A; Rahmani, O
Abstract: In this study, free vibration analysis of magneto-electro-thermo-elastic (METE) nanobeams resting on a Pasternak foundation is investigated based on nonlocal theory and Timoshenko beam theory. Coupling effects between electric, magnetic, mechanical and thermal loading are considered to derive the equations of motion and distribution of electrical potential and magnetic potential along the thickness direction of the METE nanobeam. The governing equations and boundary conditions are obtained using the Hamilton principle and discretized via the differential quadrature method (DQM). Numerical results reveal the effects of the nonlocal parameter, magneto-electro-thermo-mechanical loading, Winkler spring coefficients, Pasternak shear coefficients and height-to-length ratio on the vibration characteristics of METE nanobeams. It is observed that the natural frequency is dependent on the magnetic, electric, temperature, elastic medium, small-scale coefficient, and height-to-length ratio. These results are useful in the mechanical analysis and design of smart nanostructures constructed from magneto-electro-thermo-elastic materials.